At performe eller ikke at performe: Om interaktivitet i Signas 57 Beds og The Black Rose Trick - Skjoldager-Nielsen, Kim (Peripeti, 2024)
Focusing on the experience of the audience, Kim Skjoldager-Nielsen analyzes two performances by Danish director Signa Sørensen in order to sum up some dramaturgical perspectives of this particular kind of interactive theater.